Regenerative Human Resource Development Integrating Digital Ethics to Sustain Skills Wellbeing and Organizational Longevity - Achmad Mohyi (Mandalika Institute, 2025)
This study explores the integration of Regenerative Human Resource Development (RHRD) with digital ethics to sustain skills, wellbeing, and organizational longevity. RHRD focuses on continuous employee development, fostering adaptability, and enhancing both technical and interpersonal skills. Integrating digital ethics ensures that employees are not only proficient in technology but also understand the ethical implications of digital tools and data usage. This combination helps create a responsible workforce capable of navigating technological advancements while maintaining a healthy work-life balance. The research, conducted using a library research methodology, analyzes existing literature to highlight the importance of embedding ethical considerations in HRD practices. The findings suggest that organizations that adopt RHRD with digital ethics are better equipped to sustain skills, enhance employee wellbeing, and ensure long-term organizational sustainability. This integrated approach is crucial for navigating the challenges of a rapidly evolving technological landscape.